The Influence of Psychological Games on Mental Health in Education - Vandra, Attila (European Journal of Mental Health, 2007)
The percentage of those who have mental health problems is much higher in the group of people who chose supporting occupations (teachers, psychologists, etc.), than in the whole society. Teachers need personal development as psychotherapists do. In Rumania the realisation of such a project would involve many difficulties. Because of a misbelief (education is unidirectional) there is an expectation, indeed a very strong one, that teachers adopt the role of the Rescuer, somebody who tries to solve other people’s problems, even if the other refuses help. Experimental data confirm the tendency of teachers to adopt the role of the Rescuer. Adopting this role can have two negative consequences. 1) It negatively affects the maturation process of the child and 2) it becomes a source of psychological games in which participants make efforts both to suffer and to make others suffer. For prevention, an education for maturation is necessary, which is possible only in assertive conflict solving and in OK–OK life positions. Different psychological schools are analysed. This life position is adopted by humanist psychology and by transactional analysis. The promotion of humanistic psychology or transactional analysis-based pedagogy in Rumania can be helpful, but is not the only solution and is not the solution. The problem is that humanistic Gordon pedagogy is unknown, and there are no certified transactional analysis trainers in Rumania today.